The Capitalistic in Paul Auster's Leviathan: A Cultural Materialist Reading - Seyed Hadi Momen; Fatemeh Karegar Bardaskan; Mehran Shabankhah Leayli (BIRCU, 2023)
The aim of the present research is to unveil how capitalism reading can be perceived by a Cultural Materialist Reading in the selected novel Leviathan. Paul Auster is one of those writers who is always multitasking. His stories are never about just one thing, and you can never be sure what's going on behind the scenes until you turn the last page. To put in other words, while a literary work may serve to practice the dominant ideology, it may produce a contrary dissident reading. This possibility mostly is based on the inner contradictions of any literary text. This is the common ground of cultural materialists. In Leviathan, Paul Auster has skillfully exhibited such a verbal game to represent his own concerns regarding the subject of the identity, ideology and power caught in the novels, leading to a “dissident” reading which is potentially opposed and threatening to those social oppressive norms which the protagonists “Benjamin Sachs” are suffered.